New orchids in the flora of Vietnam VI (Orchidaceae, tribes Arethuseae, Cymbidieae, Diurideae, Epidendreae, Vandeae, and Vanilleae) - Averyanov, Leonid V.; Nguyen, van Canh; Truong, Ba Vuong; Nguyen, Khang Sinh; Nguyen, Cuong Huu; Maisak, Tatiana V.; Doan, Nga Thi; Nguyen, Tuan Hoang; Pham, van The; Dat, Pham Thi Thanh; Thai, Tran Huy; Nguyen, van Khuong; et al. (Phytotaxa, 2023)
This paper presents new data on the orchid diversity of Vietnam obtained from field explorations made mainly in 2015–2022, as well as from the study of some historical collections housed at the Herbaria of Russia and Vietnam. It includes descriptions of two species new to science (Coelogyne phitamii and Cymbidium sangii), reports of one genus (Stigmatodactylus), and eleven species new to the flora of Vietnam (Coelogyne fuliginosa, C. suaveolens, Cremastra malipoensis, Cymbidium cochleare, C. goeringii, C. macrorhizon, Holcoglossum nagalandense, Miguelia shenzhenica, Otochilus lancilabius, Pelatantheria bicuspidata, Stigmatodactylus sikokianus). Three new nomenclature combinations (Biermannia averyanovii (Vuong, Kumar, V.H.Bui & V.S.Dang.) Aver., Miguelia shenzhenica (Z.J.Liu & S.C.Chen) Aver., Panisea sondangii (Vuong, Aver. & V.H.Bui) Aver.) and lectotypes for three species (Coelogyne suaveolens, Otochilus lancilabius, Pelatantheria bicuspidata) are proposed. Data on accepted names, main synonyms, etymology (for newly described species), morphological description, studied specimens, ecology, phenology, and distribution, conservation status assessment according to IUCN Red List Categories and Criteria, brief taxonomic notes, and illustrations are provided for each species listed.